La experiencia de ser tutor desde una visión esencial, reflexiones de docentes de la Universidad Santiago de Cali - Acosta Ocampo, Cilia Inés (Universidad Santiago de Cali, 2017)
This document contains the systematization of the research, the experience of being a tutor from an essential perspective. Three teachers of the Universi-dad Santiago de Cali undertook this exercise; they lived the research from the phenomenological method, which enabled them to understand tutoring as a space to Be in relation to the Others. The documents begins with a synthesis of several national and international research related to the experience of mentoring in higher education, which manages to recognize that mentoring has been an academic experience that allows the improvement of the performance of professionals in formation.